’Keeping Going’: Alquimia, violencia y sacrificio en la poesía de Seamus Heany - Raez Padilla, Juan (Miscelánea: A Journal of English and American Studies, 2008)
The first part of this article analyses some values of the symbolism of alchemy which are then applied, in its second part, to the study of the poetry of Seamus Heaney. It highlights such aspects as the interrelationship between earthy materialism and airy spirituality, between upward and downward movement, as well as the sublimation of purity in and through impurity and dirtiness. Taking these symbolic values into consideration, we proceed to analyse in Heaney’s work —especially in his poem “Keeping Going”— the imagery of mud, dung and lime. The last of these will lead to the discussion of the symbolism of alchemiyn the poetry of the Northern Irish Nobel Prize winner: the transmutation of dirtiness into whiteness; the distillation of hope out of distress; the evocation of violence and sacrifice not from a motionless, undecided perspective, but from the belief in alchemic transmutation learned in the magic of everyday life.